Modeling the advective supply of Calanus finmarchicus to Stellwagen Bank as an indicator of sand lance foraging habitat, and the climate vulnerability of a National Marine Sanctuary - Cameron R. S. Thompson; Cameron R. S. Thompson; Isabel A. Honda; Isabel A. Honda; Jacob P. Kritzer; Jackie Motyka; Jeffrey A. Runge; Rubao Ji (Frontiers in Marine Science)
The northern sand lance (Ammodytes dubius), a key species in the food web supporting the Stellwagen Bank National Marine Sanctuary (SBNMS), feeds primarily on the lipid-rich copepod Calanus finmarchicus. Climate change poses a significant threat to this dynamic, as C. finmarchicus populations are at the southern edge of their subarctic distribution and are vulnerable to warming waters and changing oceanographic conditions. Declines in the advective supply of C. finmarchicus to Stellwagen Bank could adversely affect sand lance populations and, consequently, the ecological and economic resources that depend on them. To quantify the connectivity between SBNMS and potential sources of C. finmarchicus, we used the Finite-Volume Community Ocean Model (FVCOM) coupled with Lagrangian particle tracking over the years 1978 to 2016. Numerical experiments revealed that Stellwagen Bank is highly connected to upstream areas in the Maine Coastal Current (MCC), where existing time series monitoring stations observe C. finmarchicus populations. The connectivity exhibited strong seasonal patterns, with peak connectivity occurring during spring and early summer, aligning with the sand lance feeding period on C. finmarchicus. We found significant interannual variability, influenced by changes in the strength of the MCC and circulation patterns in the western Gulf of Maine. Years with stronger MCC flow showed higher connectivity and a greater potential supply of C. finmarchicus particles to Stellwagen Bank. Conversely, periods of reduced flow corresponded with decreased connectivity, potentially limiting the availability of C. finmarchicus to sand lance populations. Meanwhile, observations from drifters and buoys since 2001 have documented decreases in MCC current speed which has been linked to a climate driven strengthening of southwesterly winds. These findings underscore the importance of pelagic habitat connectivity in assessing the climate vulnerability of marine protected areas (MPAs) like SBNMS. Furthermore, monitoring C. finmarchicus populations at upstream time series stations can provide information on downstream foraging habitat in MPAs, and potentially in other vulnerable areas of ecological and socioeconomic interest. By incorporating these indicators of connectivity and upstream C. finmarchicus population abundance into decision support tools, Sanctuary managers and stakeholders can make informed decisions to mitigate potential climate impacts.